PETILASAN KAHYANGAN: MEMORY, SEJARAH DAN WISATA DI PINGGIRAN WONOGIRI - Andriyanto (Jurnal Pendidikan, Sains Sosial, dan Agama, 2021)
This research examines the intersection point between Hadiwijaya's early historiography before ascending the throne and also the memory or speech stories that developed in Kahyangan Dlepih. This researchuses the historical method by collecting sources in the form of historiography about the area, collective memory and also the development of this area into a tourist area. There is a difference between what is written in historiography and what is developed in the supporting community regarding the narrative of the Dlepih Kahyangan area. In memory and also folklore, this area is believed to be the location of Hadiwijaya's hermitage and is strengthened by the tomb of Nyai Puju, but the historiography states that the location of Hadiwijaya's hermitage is in another location and this location is considered sacred because this location is also used as one of the larung locations. offerings. The existence of narratives and traditions of larung offerings causes this area to become an area visited by religious tourists.